Allosteric regulatory enzymes - Traut, Thomas (Springer, 2008)
All enzymes have the ability to increase the rate of a chemical reaction, often by more than a billion-fold. This book covers the developments in the analysis of allosteric enzymes, focusing on those features that are invaluable to the discussion of allosterism and regulation. It describes all the mechanisms used for changing enzyme activity.